Numerical prediction of the ductile damage for axial cracks in pipe under internal pressure - Fezazi Amina Ismahne; Mechab Belad; Salem Mokadem; Serier Boualem (Fracture and Structural Integrity)
This study presents a numerical prediction of the ductile damage for axial cracks in pipe subjected to internal pressure. The three dimensional finite element methods used to evaluate the J-integral. The effect of the external radius (Rext), thickness of the pipe (t), length crack (a), applied loads (P) and crack position has studied. The Monte Carlo method was used to determine the probabilistic characteristics of the J-integral. Its also used later to predict the failure probability based on initiation of the crack growth. We note that the crack size and the geometries of the pipe are an important factor influencing on the durability of the pipe